IMPLEMENTASI ASAS-ASAS HUKUM EKONOMI SYARIAH DALAM PENGEMBANGAN MART 212 PADA 212 MART MUHAJIRIN PALEMBANG - Yogi, Yogi; fauziah, fauziah; armasito, armasito (Program Studi Muamalah Fakultas Syariah dan Hukum, 2020)
ABSTRACT 212 Mart Muhajirin Palembang is a Mart that was founded in the spirit of the Muslim community, which was initiated by the action of defending Islam against religious blasphemy. Which is the implementation of the Islamic defense action, namely by building a business in the retail trade sector. This is what motivates the author to raise the title